Analysis of Problem-Solving Abilities of Elementary School Students Through Problem-Based Learning Model Based on Self Confidence (Journal of Primary Education, 2019)
The purposes of this study are to improve students problem-solving abilities and self-confidence in the problem-based learning model and to describe the ability of students to solve mathematical problems through a problem-based learning model regarding students' confidence. This research is a mixed methods research, with an embedded experimental model. Data collection techniques used tests of problem-solving skills, confidence questionnaires, interviews, observation, and documentation. Data analysis techniques using N-Gain, Correlation Pearson and Triangulation of qualitative data. The subject of research amounted to 67 students. The results showed that there was an increase in mathematical problem-solving abilities and students' self-confidence significantly. Students' confidence have N-Gain score of 0.40 was included in the medium category, meanwhile, the students' problem-solving abilities with N-Gain scores of 0.36 included in the medium category. Students with high confidence can understand the problem, develop a problem-solving plan, implement a problem-solving plan, and recheck the results of problem-solving well, students with confidence moderate can understand the problem, develop a plan good problem solving, but less able to recheck the results of problem-solving, students with low self-confidence can understand problems, develop plans for problem-solving well, but are less able to implement problem-solving plans and are unable to recheck results of problem-solving.